Development of Centralized Real -Time Flood Detection and Warning System - KHUZAIDIN, MUHAMMAD HASSIFF (Progress in Engineering Application and Technology, 2023)
The flooding problem in Malaysia currently is very concerning even though Malaysia’s technological advancement is quite high. There are a few key problems that allow this problem to persist which are high cost of flood detection technology, lack expert manpower, and connectivity issue between different systems. The objectives to be achieved in this project are to design a suitable LabVIEW Graphical User Interface (GUI) for the centralized flood warning and prevention system, to implement the autonomous system with the developed GUI in real - time application, and to analyse the performance of the system in terms of reliability and performance. The objectives listed in this project can be achieved by developing a system that uses an ESP32 microcontroller paired with water level sensors that will send the sensor readings into Firebase Database. The readings can also be used in the LabVIEW software with the proper indicators for the graphical user interface (GUI). At the end of the project, all the collected data will be inserted into a Microsoft excel spreadsheet which can be used to plot a line graph. All in all, based on the findings made the project can considered a success but there are still some improvements that can be made such as changing the type of sensor used that has higher capability to measure the water level such as an underwater ultrasonic depth sensor.